Anti-Lift Assessment of Multi-Flap Motorcycle Winglet for Track Usage Via Wind Tunnel Test - M.I.N, Ma'arof; Nurfarah, A.Z.Kamarudin; Girma, T. Chala; Timur, Izmailov (International Journal of Emerging Technology and Advanced Engineering, 2022)
— In motorcycle racing it is important to travel at high speed. However, involuntary lift of the front wheel could occur at high speed of travelling. This results in the loss of traction, stability and control over the motorcycle. This undesired phenomenon could be minimized by adding downforce at the frontal section of the motorcycle. The aim of this study was to generate supplementary downforce via the integration of anti-lift winglet at the frontal section of the motorcycle. This study tested on the effects given by the variation on the numbers of multi-element flaps with respect to anti-lift force generated. The anti-lift winglet assisted the motorcyclist for greater control and stability during high speed of travelling by being planted onto the ground. It was observed that the highest downforce is generated by winglets with the highest number of multi-element flaps. Conclusively, the installation of the winglet on the motorcycle significantly improves control and stability during high speed of travelling by being planted onto the ground. For future studies, other parameters such as the angle of attack for the winglet and the general shape of the winglets could be examined.